1995
DOI: 10.1007/bf00010289
|View full text |Cite
|
Sign up to set email alerts
|

Citric acid in tomato plant roots and its effect on cadmium uptake and distribution

Abstract: Experiments were carried out to investigate the effects of root citric acid on uptake and initial distribution of cadmium (Cd) in tomato plants (Lycopersicon esculentum, cv. Tiny Tim). Cd was measured by "y-spectrometry, using 115Cd spikes. Citric acid was measured by UV-detection, and, after spiking with lac-citric acid, by ~-spectrometry. Cd was applied for 48 h periods, in control experiments, in the presence of citric acid, and after 24 h plant pre-incubation with citric acid.Pre-incubation resulted in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 35 publications
4
34
0
Order By: Relevance
“…In non-hyperaccumulator plants [i.e., plants which are not able to translocate and accumulate very high concentrations of one or more metal(loid)s in the shoots without showing severe toxicity symptoms (Baker et al, 2000)], the main Abbreviations: AM, arbuscular mycorrhiza; Fm, Funneliformis mosseae; GSH, reduced glutathione; PC, phytochelatin.detoxification mechanism of Cd is the complexation with thiolpeptides and the subsequent sequestration in the vacuoles of root cells (Verbruggen et al, 2009). Acropetal Cd translocation from root to shoot takes place through the xylem vascular elements, following the transpiration-driven water flow, possibly both in free and complexed form, such as Cd-organic acids or Cdphytochelatins, as suggested by Senden et al (1995) in tomato, and by Gong et al (2003) in Arabidopsis thaliana, respectively.…”
Section: Introductionmentioning
confidence: 97%
“…In non-hyperaccumulator plants [i.e., plants which are not able to translocate and accumulate very high concentrations of one or more metal(loid)s in the shoots without showing severe toxicity symptoms (Baker et al, 2000)], the main Abbreviations: AM, arbuscular mycorrhiza; Fm, Funneliformis mosseae; GSH, reduced glutathione; PC, phytochelatin.detoxification mechanism of Cd is the complexation with thiolpeptides and the subsequent sequestration in the vacuoles of root cells (Verbruggen et al, 2009). Acropetal Cd translocation from root to shoot takes place through the xylem vascular elements, following the transpiration-driven water flow, possibly both in free and complexed form, such as Cd-organic acids or Cdphytochelatins, as suggested by Senden et al (1995) in tomato, and by Gong et al (2003) in Arabidopsis thaliana, respectively.…”
Section: Introductionmentioning
confidence: 97%
“…At subtoxic shoot Cd concentrations, tomato plants not previously exposed to Cd and preincubated (24 h) with 2.5 × 10 -4 M citrate increased root-to-shoot transport of 5 × 10 -6 M Cd six-to eightfold compared to no citrate addition or to the simultaneous addition of citrate and Cd (Senden et al 1995). Pre-incubation with citrate also doubled the amount of citrate collected from xylem exudates (Senden et al 1995). In another study, citrate was shown to decrease the lateral escape of Cd from xylem vessels and to reduce adsorption of Cd to xylem cell walls (Senden and Wolterbeek 1990).…”
mentioning
confidence: 93%
“…For example, organic acids in pot experiments triggered uranium accumulation in Indian mustard and Chinese cabbage , and increased chromium accumulation in tomato (Srivastava et al 1999). Under hydroponic conditions, organic acids furthermore increased the uptake of cadmium by tomato and durum wheat (Senden et al 1995;Berkelaar and Hale 2003), and of lanthanum by wheat and barley (Wang et al 2004;Han et al 2005).…”
Section: Introductionmentioning
confidence: 99%